An Evalution of the Functions Of The City Council Of George Town Penang 1957-1966 - Awang, Mat Lazin (Universiti Sains Malaysia, 1974)
The first part of the exercise deals briefly with the history of the Penang City Council until 1966. The seoond part deals with the discussion on the objectives of the local government, and the aim is to acquaint the readers with the structure of the local government so that the reader could understand the purpose of local government in Malaysia. The third and tho fourth parts deal respectively with the evaluation of the function of the City Council of George Town, Penang and make recommendations for reforms in the Council, which would likely be benaficial to the public. The final part puts the question to the readers whether we should maintain democracy at local level and at the same discussion is briefly given on the position of democracy found ln Malaysian Society.